2014
DOI: 10.1002/eji.201344244
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic‐based, live‐cell analysis allows assessment of NK‐cell migration in response to crosstalk with dendritic cells

Abstract: Migration and localization of NK cells into peripheral tissues are tightly regulated under normal and pathological conditions. The physiological importance of NK cell-DC crosstalk has been well documented. However, the ways in which DCs regulate the migratory properties of NK cells (such as chemotaxis, chemokinesis, chemo-repulsion) are not fully defined in vitro. Here, we employed a microfluidic platform to examine, at the single-cell level, C57BL/6 NK-cell migrations in a stable chemical gradient. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…We identified that CXCR3 is a key receptor on NK cells that mediated the migration. More interestingly, a surprising function of GM-CSF in repulsing murine NK cell migratory response was revealed in this microfluidic assay [34]. This study highlighted also key feature and difference of the two migration assays (trans-well and microfluidic assays): cell migration parameters (speed and chemotactic index) were analyzed in the microfluidic assay, at the single-cell level on a 2D plane under a stable chemical gradient; in contrast, chemotaxis was measured as a net downward movement of a population of the migratory cells in the trans-well assay.…”
Section: A Simple Microfluidic System For Imaging Of Nk Cell Traffickingmentioning
confidence: 79%
See 3 more Smart Citations
“…We identified that CXCR3 is a key receptor on NK cells that mediated the migration. More interestingly, a surprising function of GM-CSF in repulsing murine NK cell migratory response was revealed in this microfluidic assay [34]. This study highlighted also key feature and difference of the two migration assays (trans-well and microfluidic assays): cell migration parameters (speed and chemotactic index) were analyzed in the microfluidic assay, at the single-cell level on a 2D plane under a stable chemical gradient; in contrast, chemotaxis was measured as a net downward movement of a population of the migratory cells in the trans-well assay.…”
Section: A Simple Microfluidic System For Imaging Of Nk Cell Traffickingmentioning
confidence: 79%
“…Our study demonstrated the effective use of a simple microfluidic device in experimental studies of directed NK cell migration in controlled gradient environments and for quantitative cell migration data analysis at the single cell level [34]. The study revealed interesting insights regarding migratory interactions between NK cells and dendritc cells.…”
Section: Future Perspectives On Studying Nk Cell Migration Using Micrmentioning
confidence: 85%
See 2 more Smart Citations
“…One might derive exosomes from a specific DC preparation to activate NK cells in vitro to augment the ability of these NK cells in the activation of DC in vivo to promote the NK-DC crosstalk in the induction of specific immunological outcomes in future development of immunotherapy. Third, as migrating immune cells at tumor sites are critical in mounting effective antitumor activity, understanding the regulation of NK-cell or DC-cell migrations in NK-DC crosstalk can be critical in future designs of antitumor immunotherapy [59]. Abilities to upregulate specific chemokine receptors for NK-cell trafficking into the tumors will promote infiltration of NK cells at the tumor microenvironment.…”
Section: Conclusion and Future Perspectivementioning
confidence: 98%